Efficient delivery of BRD4 inhibitor by glutathione-sensitive nanoparticle to suppress gallbladder cancer through inhibiting NF-κB signaling. (December 2020) - Xu, Qiongcong; Wang, Liying; Tong, Tong; Huang, Xitai; Huang, Chensong; Li, Fuxi; Su, Qiao; Tien, Yichih; Wu, Jun; Zhao, Wei; Yin, Xiaoyu
Highlights: A redox-responsive nanoparticle system based on L-cysteine-based poly(disulfide amide) (Cys-8E Polymer) was implemented to achieve targeted delivery of therapeutic agents into gallbladder tumor. BRD4 Inhibitor (JQ1) was effectively encapsulated by Cys-8E Polymer at a high drug loading for anti-cancer therapy. JQ1-loaded Cys-8E nanoparticles (JQ1@Cys-8E NPs) significantly suppressed gallbladder tumor growth in vitro and in a PDX model of early recurrence with negligible systemic toxicity. JQ1@Cys-8E NPs enhanced the therapeutic effect of JQ1 through inhibiting NF-κB pathway. Abstract: Gallbladder cancer (GBC) is one of the most common and aggressive biliary tract diseases with limited therapeutic strategies and poor prognosis. Various therapeutic agents have been demonstrated effective in preclinical models, but high dose requirement and toxicity to normal cells limit their clinical applications. Considering the high concentration of glutathione (GSH) in GBC, we developed a GSH-responsive nanoparticle (NP) system based on biodegradable poly(disulfide amide) (Cys-8E Polymer) for targeted delivery of a BRD4 inhibitor (JQ1), which is known as a promising therapeutic agent for GBC treatment. JQ1-loaded Cys-8E nanoparticles (JQ1@Cys-8E NPs) possessed a high JQ1 loading, preferable stability and redox-responsive release behavior. Additionally, the NPs showed good targeted delivery into GBC tumor spheroids and GBC patient-derived xenograft (PDX) tumors. Specifically, the intracellular GSH in tumors could trigger the release of JQ1, which induced the cell cycle arrest and apoptosis of GBC cells. RNA-sequencing analysis revealed that JQ1@Cys-8E NPs enhanced the effect of JQ1 through inhibiting NF-κB pathway. Importantly, JQ1@Cys-8E NPs significantly suppressed GBC tumor growth in the PDX model of early recurrence. No obvious systemic toxicity and organ damages were observed after treatment with JQ1@Cys-8E NPs. Our results demonstrate the promising therapeutic applications of JQ1@Cys-8E NPs for adjuvant therapy in GBC treatment.